Efectos socioeconómicos en los beneficiarios del proyecto del servicio de agua para riego, sector del río Versalles, distrito de Ocobamba – Cusco 2023 - Aquise Vargas, Carlos Arturo (2025)
The lack of water for agriculture in Peru affects production and food security. In Cusco, the MERISS Plan aims to support farmers by improving water infrastructure and providing technical training. However, some farmers are not interested in participating, limiting the programme’s impact and perpetuating economic vulnerability. Irrigation stands out as an essential driver of socio-economic development. The project ‘Improvement and Expansion of Irrigation Water Services in the Versalles River Sectors’ seeks to address this need. The objective was to understand the socio-economic effects on beneficiaries caused by the implementation of the ‘irrigation water service in the Versalles River sectors’ project. The methodology was qualitative with a non-experimental ethnographic design. The sampling procedure was intentional convenience sampling and saturation point sampling, with a total of 15 informants. Data collection was carried out through in-depth interviews, document review, and participant observation. The results reveal that the project not only increases agricultural productivity and farmers’ incomes, but also strengthens local food security for beneficiaries engaged in agriculture. In conclusion, despite challenges such as the lack of organisation in the communities of San José and Santa Elena-Nueva Granada and limited access to water due to the lack of a water distribution system, this irrigation initiative offers opportunities to improve living conditions and promote sustainable development in the Cusco region.